Analisis Pengaruh Debt To Asset Ratio (DAR) dan Debt To Equity Ratio (DER) Terhadap Return On Asset (ROA) pada PT Gudang Garam, Tbk Periode 2013 - 2022 - Fitria, Nurul Ayu; Yanuari, Yayan; Sugiyanta, Yohanes (Mulia Pratama, 2024)
This study aims to determine the effect of debt to asset ratio and debt to equity ratio on return on assets at PT Gudang Garam Tbk. This type of research is descriptive quantitative. The population used is the financial statements of PT Gudang Garam Tbk from 2013-2022. Data collection techniques in this study are documentation techniques and data analysis used includes: financial ratios with debt to asset ratio (DAR), debt to equity ratio (DER), and return on assets (ROA), descriptive tests, classical assumption tests, hypothesis tests and multiple linear regression tests. Based on the test results In the T test (partial) The effect of the Debt to Asset Ratio variable with Return On Asset obtained a t count value of -3.149 and t table has a value greater than 2.306. Thus t count -3.149 <t table 2.306 and has a significant figure of 0.016 <0.05. so it can be concluded that, H1 is accepted and Ho is rejected, which means there is a significant negative influence (opposite direction) between Debt to Asset Ratio and Return On Asset, while based on the test results In the T test (partial) the t value for the Debt To Equity Ratio variable is t count 3.134> t table 2.306 and has a significant number of 0.017 <0.05 so it can be concluded that, H2 is rejected which means there is a significant positive influence between Debt To Equity Ratio and Return On Asset. The results of the F test (simultaneous), Debt To Asset Ratio and Debt To Equity Ratio have a significant effect on Return On Asset with a contribution of 87.3%. This is also reinforced by the results of the F count value (4.969)> F table (4.74).